Sobre(viver) pós-Covid-19: Escuta analítica acerca das ressonâncias da pandemia nos corpos - Martins, Yolanda Luiza de Castro (2023)
In March 2020, the World Health Organization declared a Covid-19 pandemic, a phenomenon that affected all countries and claimed over 6 million lives worldwide. An invisible biological agent with abrupt and deadly characteristics impacted lifestyles, exposed pre-existing social inequalities, and mobilized countries to devise economic strategies to contain the wounds caused by the health crisis, not without effect: social distancing, fear of contamination, death of oneself or loved ones could be experienced as traumatic events, leaving individuals feeling unsupported due to a reality that imposes itself, forcing them to respond in a unique way to the contingencies of the pandemic. Taking into account this scenario and from a psychoanalytic perspective, an investigation was conducted to explore the resonances of the pandemic's reality in the bodies of those who became infected, considering that the individual is located as a body and is equivalent to the Ego, as found in the writings of Freud and later developed by Lacan and contemporaries. Psychoanalytic listening was chosen as the methodology to guide the conducting of interviews with 10 volunteers for the study. The interviews were recorded in audio format for subsequent transcription and analysis of the material. For analysis purposes, the contamination process was divided into two stages: 1) the rupture caused by the pandemic and the virus, and 2) the possibilities of reorganization due to the imposed disorganization. Finally, we aim to reflect on the reverberations of subjectivating and desubjectivating effects of trauma present in the individuals' psychic work.